'Climategate' fallout: shadow of suspicion falls across East Anglia. - Corbyn, Zoë (Times Higher Education, 2010)
The article reveals that researchers at the University of East Anglia (UEA) who are not into climate change studies are being affected by the 'Climategate" scandal where thousands of e-mails and documents were hacked from a server of the Climatic Research Unit (CRU) of the University of East Anglia. An example was a research paper published by a professor in UEA's School of Chemistry which received online comments regarding its veracity just because it came from UEA. The CRU scientists have been accused of manipulating research data due to the scandal.